2020
DOI: 10.3389/fphar.2020.586187
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in an Older Population with Type-2 Diabetes Mellitus: Identification of the Characteristics and Healthcare Utilization of High-Cost Patients

Abstract: Objectives: Little is known about the specific comorbidities contributing to higher costs in patients with type-2 diabetes mellitus (T2DM), particularly in older cases. We aimed to evaluate the prevalence, type, and cost of comorbidities occurring in older T2DM patients versus older non-T2DM patients, and the factors associated with high cost (HC) T2DM patients.Methods: Retrospective cohort study using information from the Campania Region healthcare database. People aged ≥65 years who received ≥2 prescriptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
5
21
1
Order By: Relevance
“…We found a skewed distribution of expenditures related to specialist care, as well as medication use, and that mean per patient expenditures were consistently higher than median per patient expenditures. Prior research has also recognized this skewed distribution of costs, as a disproportional amount of the economic burden of type 2 diabetes was found to be attributable to a minority of patients [17,[39][40][41][42][43]. This could result from the focus on treating patients' emergent problems or could be due to the presence of multiple complications in patients with advanced diabetes, as well as comorbidities [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a skewed distribution of expenditures related to specialist care, as well as medication use, and that mean per patient expenditures were consistently higher than median per patient expenditures. Prior research has also recognized this skewed distribution of costs, as a disproportional amount of the economic burden of type 2 diabetes was found to be attributable to a minority of patients [17,[39][40][41][42][43]. This could result from the focus on treating patients' emergent problems or could be due to the presence of multiple complications in patients with advanced diabetes, as well as comorbidities [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…This could result from the focus on treating patients’ emergent problems or could be due to the presence of multiple complications in patients with advanced diabetes, as well as comorbidities [ 39 , 40 ]. Moreover, previous studies have found that factors such as the presence of obesity, insulin use, renal impairment, and hospitalization predict high costs for patients with diabetes [ 17 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the gradual reduction of family size and the disintegration of the traditional large family structure, the function of family endowment is gradually weakened, and the elderly cannot get direct living care (42). Comorbidities are common in older adults with diabetes, more than 97% of them had at least one of the comorbidities (43). Comorbidities not only increase the health care needs, utilization and mortality of people with diabetes (44)(45)(46), they also increase the complexity of disease management and the burden of self-management (47,48) which is a challenge for empty-nester patients to cope with.…”
Section: Discussionmentioning
confidence: 99%
“…In the past three decades, the prevalence of type 2 diabetes mellitus (T2DM) has increased dramatically and has become an important global health problem. 1–4 In 2017, ∼5 million deaths worldwide were attributable to diabetes. One of the major concerns is that more than 80% of people with T2DM live in low- and middle-income countries, accounting for 90–95% of all diagnosed cases that do not require insulin treatment.…”
Section: Introductionmentioning
confidence: 99%